2016
DOI: 10.18632/oncotarget.10909
|View full text |Cite
|
Sign up to set email alerts
|

Occult HBV infection in HCC and cirrhotic tissue of HBsAg-negative patients: a virological and clinical study

Abstract: AimTo evaluate the virological and clinical characteristics of occult HBV infection (OBI) in 68 consecutive HBsAg-negative patients with biopsy-proven cirrhosis and HCC.MethodsHBV DNA was sought and sequenced in plasma, HCC tissue and non-HCC liver tissue by PCRs using primers for HBV core, surface and x regions. OBI was identified by the presence of HBV DNA in at least two different PCRs.ResultsOBI was detected in HCC tissue of 13 (20%) patients and in non-HCC liver tissue of 3 of these 13. OBI was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 31 publications
3
70
1
Order By: Relevance
“…The DNA extracted was analysed for the presence of HBV DNA by polymerase chain reaction (PCR) using sets of primers for core, as previously reported . In HBV DNA‐positive plasma, the HBV genotype and the mutations in the HBV pre‐S/S coding and pol regions were determined by automated sequencing, as previously described …”
Section: Methodsmentioning
confidence: 99%
“…The DNA extracted was analysed for the presence of HBV DNA by polymerase chain reaction (PCR) using sets of primers for core, as previously reported . In HBV DNA‐positive plasma, the HBV genotype and the mutations in the HBV pre‐S/S coding and pol regions were determined by automated sequencing, as previously described …”
Section: Methodsmentioning
confidence: 99%
“…OBI is defined as the persistence of HBV DNA in the serum or liver of individuals with undetectable HBsAg using currently available assays . It has been suggested that OBI is related to misdiagnosis, disease progression, poor blood transfusion safety, HBV reactivation, and vaccination failure …”
Section: Introductionmentioning
confidence: 99%
“…All patients had been treated with a DAA regimen according to the HCV genotype, international guidelines and local availability in 19 clinical centres in Campania, southern Italy. These centres had cooperated in several clinical investigations using the same clinical approach . In the study period, these 19 centres treated by DAA regimen 3259 anti‐HIV negative subjects, with virological failure in 129.…”
Section: Methodsmentioning
confidence: 99%